Leporidae Fischer 1817 - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
Family LEPORIDAE (HARES AND RABBITS) • Small to medium-sized lagomorphs with short fluffy tails, soft thick pelage, and large eyes; ears project upward; hindlimbs longer than forelimbs. • 23-68 cm. • Holarctic, Afrotropical, Indo-Malayan, and Neotropical Regions. • Forests, shrubby areas, grasslands, deserts, tundra, alpine slopes, and agricultural landscapes up to 5400 m. • 11 genera, 63 species, 269 taxa. • 2 species Critically Endangered; 7 species Endangered; b species Vulnerable; no species Extinct since 1600. Published as part of Don E. Wilson, Thomas E. Lacher, Jr & Russell A. Mittermeier, 2016, Leporidae, pp. 107-148 in Handbook of the Mammals of the World – Volume 6 Lagomorphs and Rodents I, Barcelona :Lynx Edicions on page 107, DOI: 10.5281/zenodo.6625539